Motion analysis of front crawl swimmer's hands and the visualization of flow fields using PIV - Yamada, K.; Matsuuchi, K.; Nomura, T.; Sakakibara, H.; Shintani, H.; Miwa, T. (Biomechanics and Medicine in Swimming X, 2006)
Flow fields around a swimmer are extremely unsteady. Top swimmers are expected to swim by using effectively unsteady flow force. A motion analysis can evaluate the unsteady motion quantitatively. In addition, PIV (Particle Image Velocimetry) can visualize the unsteady flow field. With this method, the vortex motion around a hand can be evaluated quantitatively. Our study is to clarify the relationship between the vortex behavior and the motion of a hand in crawl swimming by using the motion analysis combined with PIV. The analysis is made for two subjects; one is a male with no competitive career (subject 1) and the other a female Olympic swimmer (subject 2). It was found that the hand motion in swimming was closely related to the vortex generation.